(untitled) (Czech Journal of International Relations, 1992)
On June 25, 1991, the authorized representatives of the governments of Czechoslovakia and the Soviet Union signed a protocol for the termination of Soviet troops stationed in Czechoslovakian territory. The occupation of Czechoslovakia by the Soviet Army and the ensuing political, ideological, economic and cultural influences of Soviet power over our internal affairs have become a thing of the past, once and for all. The unbelievable bas become a reality. This act took place not against the will of the Soviet government, but in accordance with its resolution that described the entry of the Warsaw Treaty armies into our territory in 1968 as a political mistake. This strengthens the hope that it will be possible to transform the sinister ties amongst the countries of the former Eastern bloc into one built on solid relations, fully respecting state sovereignty and the rights to their own political, cultural and social orientations. The Federal Assembly Commission for Supervision of the Withdrawal of Soviet troops from Czechoslovakia realized three main priorities in its work. First - to follow solutions of the technical aspects of the withdrawal and the adherence to the timetable worked out by the authorized representatives of the two countries. Second - to take part in the preparatory work on an agreement for the settlement of property and financial claims ensuing from the entry, presence and withdrawal of Soviet troops. Third - to strive to transform political, cultural and economic relations with the Soviet Union, and not to contribute to further destabilization of relations amongst the counties of the former Eastern bloc.